Mengungkap Kesadaran Peran Akuntan Pendidik : Perspektif Teori Tindakan Hannah Arendt - Mahmudah, Nufidatul (Jurnal Ilmiah Raflesia Akuntansi, 2024)
<!--StartFragment--><span lang="EN-US" style="font-size: 10.0pt; font-family: 'Arial',sans-serif; mso-fareast-font-family: SimSun; mso-font-kerning: 8.0pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">To produce accounting graduates that meet industry demands, the quality of their educators plays a significant role. If the quality of the accounting educators is high, then the quality of the graduates will also be high, and vice versa. In reality, the primary cause of the gap between the expectations of accounting graduates and their actual skills lies in the educators' lack of proficiency and competence in preparing graduates for successful careers. Based on this, the researcher seeks to explore the awareness of lecturers in the Sharia Accounting Study Program regarding their role as accounting educators. To examine this awareness, the researcher employs Edmund Husserl's transcendental phenomenology study. The results of this research indicate that the awareness of the role of accounting educators consists of providing engagement, training, and role modeling for students. When related to Hannah Arendt's theory of action, these roles are sequentially categorized as labor, work, and action awareness. On the other hand, when linked to Agus Mustofa's theory of consciousness, these roles align sequentially with sensory, rational, and spiritual theories. This research is expected to serve as a reference for Al Qolam University Malang in evaluating the role awareness of accounting educators in the learning process. After understanding this concept, the University should provide training and support to enhance the quality of accounting educators, enabling them to reach a higher level than they currently possess.<!--EndFragment-->